Pengaruh Struktur Kepemilikan dan Kualitas Audit Terhadap Kinerja Perusahaan - Ella Anastasya Sinambela; Eny Rachmawati; Elisabeth Anggi Febriyanti; Elly Joenarni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The company's progress can be seen from the percentage of achievement of the previously planned goals. This success will have an impact on the assessment of the company's performance. The development of company performance is influenced by various factors. The ownership structure of the company will affect the company's performance with the economic decisions made. In addition, another factor is audit quality because economic decisions are taken based on information from the company's financial statements. The purpose of this study was to determine the role of ownership structure and audit quality in the formation of company performance. Data were obtained by distributing questionnaires to several companies in three districts in East Java. The number of respondents obtained is 33 respondents. The data was then processed using SPSS with multiple linear regression analysis. The results showed the role of ownership structure in the movement of company performance partially showed a significant role. The same result is obtained by audit quality which has a significant role in the development of company performance. The company's performance is simultaneously significantly affected by the ownership structure and audit quality